Editorial: REGION - the online open-access journal of ERSA - Julia Koschinsky; Sierdjan Koster; Roberto Patuelli; Vicente Royuela; Vassilis Tselios (REGION, 2014)
This editorial launches REGION, the new online and open-access journal of ERSA. REGION aims to be a high-quality academic journal in the field of regional science. To its contributors, it offers a solid peer-review process and immediate publication upon acceptance. Also, it will be a flexible outlet, not bound by traditional journal formats or strict page limits. To its readers, the journal offers high-standard publications on current issues in regional science that are easily accessible through its website. Both submitting to the journal and accessing the contributions are free of charge to everyone.
Keywords: 330; Editorial; Open Access Journal; Open Source; Regional Science; Regional Science; Regional Economics; Economic Geography; Urban Economics; World